An analysis of anti-corruption corporate disclosure according to GRI standards in Peruvian companies / Julio Hernández-Pajares - Hernandez Pajares, Julio (UiTM Press, 2023)
This research aimed to analyse the anti-corruption policies and management disclosed following the GRI anti-corruption standard, in the sustainability reports of Peruvian companies within the framework of the institutional theory. This exploratory study used a quantitative and qualitative descriptive research design for the content analysis of the voluntary sustainability reports for 2018-2019 according to the GRI standard. The results indicated that most companies considered the disclosure of anti-corruption policies in their sustainability management approach and commitment to regulatory compliance, although without reaching a high level of compliance with the performance categories of the standard. Companies focused primarily on communicating training on anti-corruption policies and procedures to stakeholders. A significant level of disclosure is in sectors vulnerable to corruption with considerable institutional influence on policy and regulatory compliance. In Peru and other Latin American countries, governments and regulators must promote anti-corruption reporting standards to companies as part of their corporate sustainability objectives.